Effects of interleukin-2 on IL-2, IL-18, RANTES and MIP-1alpha mRNA productions in HIV infected patients - Chalinthorn Sinthuwattanawibool (Chulalongkorn University, 2009)
Thesis (M.Sc.)--Chulalongkorn University, 1998